Penerapan Media Power Point Melalui Teams Untuk Meningkatkan Hasil Belajar Tematik Pada Siswa Kelas IV Sekolah Dasar - Yuli Kristiani (Universitas Sebelas Maret, 2020)
Thematic learning activities can be developed through face-to-face learning activities either directly in class or through online learning. In recent months Indonesia has been affected by the COVID-19 virus pandemic. Teachers in online learning are required to make adjustments to their learning activities and innovate in order to continue to provide the best learning services. The type of research conducted is classroom action research. The subjects of this study were 4th grade students of SD Negeri 1 Ngaglik. The number of students in one class is 20 children. The number of male students is 9 people while there are 11 female students. Based on the results of research and discussion, it can be concluded that the application of powerpoint media through Teams online learning can improve thematic learning outcomes of fourth grade students of SD Negeri 1 Ngaglik, Wonogiri Regency, Semester 1 of the 2020/2021 Academic Year. This can be seen in the increase in the number of students who achieved the KKM score in the first cycle or by 80 %, then 19 students in the second cycle or 95 %. Based on the results of the comparison of student learning outcomes in cycle I and cycle II, it appears that there is an increase from 80% to 95%. Therefore, based on the indicators of research success that have been determined, this research has been said to be successful.